Solar-Powered Solutions for the Water and Energy Shortage Problem: The Case Study of Nahr El Bared, Lebanon - Kassem, Youssef; Gokcekus, Huseyin; Albakoush, Ismail Ataher Ab; Abdullah, Kareemah Sh. Basheer (Engineering, Technology & Applied Science Research, 2023)
Solar power is an effective way to reduce the dependency on conventional fuels and mitigate the water and energy shortage issue. The main aim of the current paper is to assess and compare the techno-economic feasibility of rooftop grid-connected photovoltaic energy systems for generating electricity and generating drinkable water in Nahr El Bared, Lebanon. To this aim, the present paper first reviews previous scientific studies associated with the water resources and energy situation to summarize the current status in Lebanon. According to this review, Lebanon’s water resources are highly polluted, domestic and industrial sewage is largely untreated, and intolerable agricultural practices further exacerbate the situation. Furthermore, population and economic growth and the continuous utilization of old power plants have led to an increase in the number of hours of power outages in the country. Accordingly, the proposed project aims to evaluate the viability of using solar energy as an alternative solution to the shortage of water and energy in the country. Secondly, the techno-economic performance of the proposed system in the selected region was evaluated based on the variations in financial parameters using RETScreen Experts software. The results demonstrate that 11770–13451kWh/yr could be generated from the solar system, which can help reduce the energy shortage and generate drinkable water. Furthermore, the investment was found to be economically viable and attractive for investors. This paper concludes that solar energy can be able to solve the energy shortage of electricity, reduce the country’s electricity costs, and produce freshwater for drinking and domestic use in the country.